The seagrass holobiont: understanding seagrass-bacteria interactions and their role in seagrass ecosystem functioning. Issue 6 (18th March 2019) - Tarquinio, Flavia; Hyndes, Glenn A; Laverock, Bonnie; Koenders, Annette; Säwström, Christin
ABSTRACT: This review shows that the presence of seagrass microbial community is critical for the development of seagrasses; from seed germination, through to phytohormone production and enhanced nutrient availability, and defence against pathogens and saprophytes. The tight seagrass-bacterial relationship highlighted in this review supports the existence of a seagrass holobiont and adds to the growing evidence for the importance of marine eukaryotic microorganisms in sustaining vital ecosystems. Incorporating a micro-scale view on seagrass ecosystems substantially expands our understanding of ecosystem functioning and may have significant implications for future seagrass management and mitigation against human disturbance. Abstract : The proposed minireview uses the holobiont concept to highlight the importance of seagrass microbiome in sustaining seagrass ecosystems and the need to include microbiome in future seagrass management and/or restoration plans.